Carotid Artery Stenting: Technical Considerations - Vitek, Jiri J.; Roubin, Gary S.; Al-Mubarek, Nadim; New, Gishel; Iyer, Sriram S. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Carotid endarterectomy (CEA) is one of the most frequently performed operations in the United States. To offer patients a less invasive means to achieve the same goal, carotid artery stenting (CAS) is investigated as an alternative treatment to CEA.METHODS: Three hundred ninety patients underwent CAS, with 451 vessels treated. CAS was performed using a coaxial system with a 7F 90-cm sheath for predilation, stent placement, and stent dilation. Pretreatment antiplatelet therapy was administered. We currently practice same-day admissions and 23-hour discharges.RESULTS: The technical success rate was 98%. The 30-day mortality/morbidity rates were as follows: death, 1.7% (two [0.5%] neurologic and five [1.2%] systemic] major strokes, 0.9% (two of four were related to the intervention); minor strokes, 5.5%. Among 25 patients who suffered minor strokes, 14 achieved complete recovery. On an annual basis, the incidence of minor stroke declined from 6.8% (1994–1995), to 5.8% (1995–1996), 5.3% (1996–1997), and then 4% (1997–1998), with no major strokes or neurologic deaths occurring during the 1997 to 1998 period.CONCLUSION: CAS is an effective treatment for carotid stenosis. With proper selection of patients and meticulous technique, complication rates compare favorably with those of CEA.